Application of Zebrafish Models in Inflammatory Bowel Disease - Hanyang, Li; Xuanzhe, Liu; Xuyang, Chen; Yujia, Qiu; Jiarong, Fu; Jun, Shen; Zhihua, Ran (Frontiers in Immunology, 2017)
Inflammatory bowel disease (IBD) is a chronic, recurrent and remitting inflammatory disease with unclear etiology. As a clinically frequent disease, it can affect individuals throughout their lives, with multiple complications. Unfortunately, traditional murine models are not efficient for the further study of IBD. Thus, effective and convenient animal models are needed. Zebrafish have been used as model organisms to investigate IBD because of their suggested highly genetic similarity to humans and their superiority as laboratory models. The zebrafish model has been used to study the composition of intestinal microbiota, novel genes and therapeutic approaches. The pathogenesis of IBD is still unclear and many risk factors remain unidentified. In this review, we compare traditional murine models and zebrafish models in terms of advantages, pathogenesis and drug discovery screening for IBD. We also review the progress and deficiencies of the zebrafish model for scientific applications.